1983
DOI: 10.1128/iai.42.2.659-667.1983
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between oxygen tension and subgingival bacterial flora in untreated human periodontal pockets

Abstract: The predominance of anaerobic bacteria in subgingival plaque samples suggests that the pocket environment is anaerobic. In the present investigation, a small oxygen tension (PO2) electrode was inserted into the base of the pocket and the P02 was recorded. In addition, the plaque in these pockets was examined culturally and microscopically. The oxygen tension at the bottom of 36 pockets (5 to 10 mm in depth) ranged from S to 27 mmHg (1 mmHg = 133.3 Pa) with a mean value of 13.3 mmHg. Moderate pockets (5 and 6 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
72
1

Year Published

1988
1988
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(76 citation statements)
references
References 31 publications
3
72
1
Order By: Relevance
“…Significant local environmental changes occur during the development of periodontal pockets (Loesche et al 1983), which may be especially deep around equine cheek teeth (Cox et al 2012). The anaerobic or partially aerobic environment of deep human periodontal pockets encourages invasion and proliferation of microaerophilic organisms, anaerobes and spirochetes, while the environment of the general oral cavity supports a significantly different microbiota (Loesche et al 1983).…”
Section: Bacteria In Oral Health and Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Significant local environmental changes occur during the development of periodontal pockets (Loesche et al 1983), which may be especially deep around equine cheek teeth (Cox et al 2012). The anaerobic or partially aerobic environment of deep human periodontal pockets encourages invasion and proliferation of microaerophilic organisms, anaerobes and spirochetes, while the environment of the general oral cavity supports a significantly different microbiota (Loesche et al 1983).…”
Section: Bacteria In Oral Health and Diseasementioning
confidence: 99%
“…Significant local environmental changes occur during the development of periodontal pockets (Loesche et al 1983), which may be especially deep around equine cheek teeth (Cox et al 2012). The anaerobic or partially aerobic environment of deep human periodontal pockets encourages invasion and proliferation of microaerophilic organisms, anaerobes and spirochetes, while the environment of the general oral cavity supports a significantly different microbiota (Loesche et al 1983). Another hypothesis that can be applied to the diseased oral microbiome is the keystone pathogen hypothesis, which maintains that certain pathogens existing at low abundance in the oral cavity may modulate their environment, disturbing the normally symbiotic relationship between the bacteria of the oral cavity, creating a state of dysbiosis (dysregulation of commensal oral bacteria) thus contributing to the development of inflammatory disease.…”
Section: Bacteria In Oral Health and Diseasementioning
confidence: 99%
“…Studies have demonstrated that tubule invasion is associated with specific bacterial cell wall-polypeptide interactions with unmineralized collagen (Love et al 1997) and other bacteria (Love et al 2000), and bacterial interactions with various molecules found in tissue fluid, dentinal fluid and saliva (Love 2001(Love , 2002. The presence of an appropriate nutritional supply in the environment influences bacterial growth (Loesche et al 1983, ter Steeg et al 1987 and may influence disease progression. Studies examining the bacterial flora of carious coronal dentine show that facultative species that primarily obtain energy from fermenting carbohydrates, for example Streptococcus spp., are mainly located in superficial dentine whilst fastidious obligate anaerobic bacteria that can metabolize host-derived amino acids and peptides, such as Peptostreptococcus micros and Prevotella intermedia, are located in deeper dentine (Edwardsson 1987, Ozaki et al 1994.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of the isolates from subgingival samples belong to Gram-negative, anaerobic rods [3][4][5][6], indicating that the periodontal pocket is a predominantly anaerobic environment. Yet, measurable quantities of oxygen have been demonstrated in such pockets [6,7]: oxygen tensions ranged from 7 to 36 mbar with a mean value of 18 mbar (1.8% 02). Moreover, a relationship between the actual pO 2 values and microbial communities in the pockets was observed [6].…”
Section: Introductionmentioning
confidence: 99%
“…Yet, measurable quantities of oxygen have been demonstrated in such pockets [6,7]: oxygen tensions ranged from 7 to 36 mbar with a mean value of 18 mbar (1.8% 02). Moreover, a relationship between the actual pO 2 values and microbial communities in the pockets was observed [6]. Therefore, the physiological response of subgingival anaerobic organisms to low oxygen tensions may represent one of the possible key properties to survival or predominance in the microbial community of periodontal pockets.…”
Section: Introductionmentioning
confidence: 99%